Let
f
be a function satisfying
f
(
x
+
1
)
−
f
(
x
)
=
1
for all
x
.
What is
f
(
2
0
1
6
)
−
f
(
−
2
0
1
6
)
?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
f ( x + n ) − f ( x ) = n , n ∈ I can be proven by induction.
Log in to reply
This could be alternately proved by adding equations in a similar manner as above also.. :-)
The function f ( x ) can be easily seen as the function y = x . Therefore, the expression turns into 2 0 1 6 − ( − 2 0 1 6 ) = 4 0 3 2 .
Yes, f ( x ) = x is a possible function of f ( x ) , but does it mean that it is the only solution for f ( x ) ? Maybe there is another function of f ( x ) such that f ( 2 0 1 6 ) − f ( − 2 0 1 6 ) = 4 0 3 2 ?
The value of the difference is constant for a fixed difference in the input, x, i.e. 1 in both cases. That means f must be a linear function, and clearly its slope is 1: f(x) = x+b f(2016) = 2016+b f(-2016) = -2016+b
So f(2016)-f(-2016) = 4032
How can we be sure that f ( x ) is not a piecewise function? i.e. f ( x ) = x + ( f r a c ( x ) 2 ) , where f r a c ( x ) denotes the fractional part of x ?
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Telescoping Series - Sum
f ( 2 0 1 6 ) − f ( 2 0 1 5 ) = 1 f ( 2 0 1 5 ) − f ( 2 0 1 4 ) = 1 f ( 2 0 1 4 ) − f ( 2 0 1 3 ) = 1 ⋯ ⋯ ⋯ ⋯
f ( − 2 0 1 3 ) − f ( − 2 0 1 4 ) = 1 f ( − 2 0 1 4 ) − f ( − 2 0 1 5 ) = 1 f ( − 2 0 1 5 ) − f ( − 2 0 1 6 ) = 1
Adding all these equations we get:-
f ( 2 0 1 6 ) − f ( − 2 0 1 6 ) = 4 0 3 2
Generalisation:- f ( x ) − f ( − x ) = 2 x